Les formes de la concurrence autour de l’orgue italien de la Renaissance - Hugo Perina (Les Cahiers de Framespa)
Organ builders and the civic and religious communities that use them rely on a set of uses and models that reveals both the will to surpass and the desire to imitate a model considered to be excellent. This article proposes a typology of the forms of competition linked to the organ and to the different actors in its production, from the craftsmen to the customers, including the evaluators. Since the value of an organ cannot be fixed according to strictly material considerations, the phenomena of competition also occur in the immaterial register. The craftsmen are valued in the same way as their production, whose quality makes its reputation. A sort of hierarchy emerges between organ builders on the basis of their capacity to respond to a set of standards whose models are the pre-existing instruments. Political and spiritual, the sound of the instrument is supposed to promote the unity of society (concord) and to participate in the policy of magnificence of the various powers active in the Italian cities of the Renaissance.